2021
DOI: 10.5483/bmbrep.2021.54.5.270
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi complex: a hub of the secretory pathway

Abstract: The Golgi complex plays a central role in protein secretion by regulating cargo sorting and trafficking. As these processes are of functional importance to cell polarity, motility, growth, and division, there is considerable interest in achieving a comprehensive understanding of Golgi complex biology. However, the unique stack structure of this organelle has been a major hurdle to our understanding of how proteins are secreted through the Golgi apparatus. Herein, we summarize available relevant research to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 80 publications
1
30
0
1
Order By: Relevance
“…This polarized transport also has recycling machinery capable of transporting back to the ER some ER‐resident proteins that left this organelle through the COPII‐coated vesicles [5]. The retrograde transport is mediated by the COPI‐coated vesicles, which are also responsible for transporting the secretory cargo through the Golgi cisternae [5–7]. In general lines, the transport of proteins between organelles within the secretory pathway occurs via spherical membrane‐bound vesicles that bud from a donor organelle and fuse with an acceptor in another part of the cell (Fig.…”
Section: Figmentioning
confidence: 99%
“…This polarized transport also has recycling machinery capable of transporting back to the ER some ER‐resident proteins that left this organelle through the COPII‐coated vesicles [5]. The retrograde transport is mediated by the COPI‐coated vesicles, which are also responsible for transporting the secretory cargo through the Golgi cisternae [5–7]. In general lines, the transport of proteins between organelles within the secretory pathway occurs via spherical membrane‐bound vesicles that bud from a donor organelle and fuse with an acceptor in another part of the cell (Fig.…”
Section: Figmentioning
confidence: 99%
“…While one of the effector clusters, EC1, mapped to a well-characterized signaling hub, the other two mapped to two essential functions, vesicular transport of proteins through the Golgi apparatus and respiratory complex assembly, both of which are highly regulated processes that may require the involvement of highly effective propagation of signals. For example, the trafficking and transport function of the Golgi apparatus is intimately related to multiple intracellular signaling pathways [ 36 , 37 ]; likewise, multiple pathways regulate the mitochondrial respiratory complex assembly [ 38 ]. Future analyses might therefore reveal the potential of the genes in EC2 and EC3 to play roles in cellular trafficking, communication and signaling that are currently under-appreciated.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that both active retention and recycling mechanisms are utilized to maintain the proper localization of Golgi resident proteins (Glick and Nakano, 2009; Rizzo et al ., 2013). The recycling of Golgi resident proteins and enzymes is mostly facilitated by COPI vesicle-mediated retrograde transport (Pelham, 2001; Cottam and Ungar, 2012; Di Martino, Sticco and Luini, 2019; D’Souza et al ., 2021; Park et al ., 2021). A balance between anterograde and retrograde transport is not only important for maintaining proper concentration of the resident Golgi proteins and lipids but also for the cell’s physiology (Blackburn, D’Souza and Lupashin, 2019; D’Souza, Taher and Lupashin, 2020).…”
Section: Introductionmentioning
confidence: 99%